ҚАРАҚАЛПАҚ ТИЛИ АРҚА ДИАЛЕКТИНИҢ БАЛЫҚШЫЛЫҚ ЛЕКСИКАСЫ - Кайпназарова, М.К. (FAN va JAMIYAT, 2020)
The article deals with the study of fishing vocabulary of the northern dialect of the Karakalpak language, wore-over Turkic languages. The usage of fishing vocabulary (fish spicies) Karakalpak nor-thern dialect with some element of Turkic vocabulary are presented with examples.